Regressão, em análise winnicottiana on-line, de pacientes adolescentes, em tempos de pandemia - Martini, Renata Leite Soares (2024)
This master's dissertation investigates the Winnicottian psychotherapeutic process in the online setting of two adolescents treated in a private therapy sessions during the Covid-19 pandemic period between 2020 and 2022. The research starts from the hypothesis that the symptoms presented by these young people suggest a poorly processed emotional development, requiring the organization of defenses throughout their lives. These defenses, to some extent, prevent the experience of a full adolescence, according to the Winnicottian proposal, due to environmental failures in the process of facilitating and sustaining the constitutive and integrative tasks of personality. Environmental failures that originate in the pre-concern and concern phases are observed in clinical cases within the depressive group. This study takes a psychoanalytic approach, composed of listening research and investigative research. It is justified by the contribution it offers to understanding the real possibility of regression to dependency and/or relative to environmental care facilitators of constitutive and integrative tasks occurring in the online setting. Regression to dependency was made possible with the co-participation of the parents, experienced within the family environment and under the therapist's guidance. However, regression in the transfer with the therapist requires further studies to confirm or not its possibility of occurrence in the online setting